Shape-controlled synthesis of cubic-like selenium nanoparticles via the self-assembly method. (20th November 2016) - Luesakul, Urarika; Komenek, Seamkwan; Puthong, Songchan; Muangsin, Nongnuj
Graphical abstract: Highlights: Shape-controlled selenium nanoparticles by self-assembly were prepared. The control effect of temperature, type and concentration of stabilizer during the fabrication of selenium nanoparticles was studied. The cubic-like selenium nanoparticles were obtained with using FA-GA-TMC as a stabilizer. The effect of shape of selenium nanoparticles on antitumor activity was investigated. Abstract: The ability to control the morphology of nanoparticles by molecular design and synthesis is gaining increasing attention for achieving improved unique properties. In this work, we designed the chemical structure of a stabilizer for controlling the shape of selenium nanoparticles (SeNPs) via a self-assembly process. When folic acid-gallic acid- N, N, N -trimethyl chitosan (FA-GA-TMC) was used as a stabilizer, SeNPs were observed to self-organize into cubic-like structures with an average size of approximately 300 nm. In contrast to the product obtained when unmodified chitosan was used as a stabilizer, this method resulted in spherical shape with an average size of approximately 200 nm. The data suggested that the cubic-like SeNPs were controlled by a combination of electrostatic interaction, π-π stacking and hydrogen bonding between neighboring particles. Furthermore, the cubic-like SeNPs exhibited good anticancer efficacy and cellular uptake against breast cancer cells while exhibiting low toxicity against normal cells. These data demonstrates a simple approach for the shape-controlled synthesis of cubic-like SeNPs for biological applications via the self-assembly method.